2021
DOI: 10.3390/ijerph18020515
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Job Insecurity on Organisational Citizenship Behaviour and Task Performance: Evidence from Robotised Furniture Sector Companies

Abstract: Over the past decade, in the light of intensive robotisation, job insecurity referring to the employees’ overall concern about the continued availability of their jobs in the future has become a hot topic. A general assumption supported by the findings is that job insecurity causes far-reaching negative consequences for the employee well-being and health, attitudes towards the job and organisation, and behaviours at work. However, the focus on behavioural outcomes, especially on employee performance at work, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 66 publications
(144 reference statements)
1
11
1
Order By: Relevance
“…Finally, further variables that we have not considered might have an impact on job performance and a role in our mediation model. Future research could test the effect of work characteristics (e.g., occupation type, income levels, job security, leadership style) and organization-based attitudes (e.g., trust in the organization, organizational identification) on job performance, and include possible moderators like job content (in the perspective of TP), and organizational culture (in the perspective of OCB) [ 77 , 78 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, further variables that we have not considered might have an impact on job performance and a role in our mediation model. Future research could test the effect of work characteristics (e.g., occupation type, income levels, job security, leadership style) and organization-based attitudes (e.g., trust in the organization, organizational identification) on job performance, and include possible moderators like job content (in the perspective of TP), and organizational culture (in the perspective of OCB) [ 77 , 78 , 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inconsistency of these findings suggests the need for a closer look at this phenomenon. Recently, Stankevičiūtė et al (2021) found that job insecurity harmed both task performance and organizational citizenship behavior. Also, Piccoli et al (2021) investigated the effect of job insecurity on job performance, hypothesizing a two-dimensional stressor framework where both hindrance and challenge effects were considered.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, the focus has often been on highlighting the harmful effects of job insecurity on both personal health and job attitudes and outcomes. However, the link between job insecurity and job performance is still unclear ( Stankevičiūtė et al, 2021 ). Therefore, focusing on exploring the potential mechanisms underlying the link between job insecurity, health, and job outcomes through intermediate drivers seems to be an area of research that needs to be addressed ( De Witte et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sharing these thoughts, Greenhalgh and Rosenblatt [70] have mentioned that if employees are facing a high level of job insecurity, they are more likely to feel less engaged toward their work and make little effort to follow and reach the organization's goals and objectives. In the same line, Presti and Nonnis [71] confirmed that employee's emotional commitment is hugely and negatively affected by job insecurity, which can also make their happiness and wellbeing inconsistent [72]. Likewise, Wang et al [73] stated that employees' job performance can be declined and decreased due to job insecurity impact, and that is why workers may feel less engaged in their work.…”
Section: Mediation Role Of Job Insecuritymentioning
confidence: 95%